The student's research companion the purpose-driven journey of scientific entrepreneurs - Aschari, Omid; Berghaus, Benjamin 1982- (Oxford University Press, 2023)
This book will aim at better understanding, elaborating on, and inspiring the creation of more purpose-driven research. It sees the potential of a thesis to be more than an examination